Pencegahan Pembiayaan Bermasalah Melalui Komite Pembiayaan - Agus Susilo; Ika Trisnawati (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2018)
One source of BMT income is the distribution of funds through Murabahah financing. Murabahah financing is a contract of sale and purchase with prices and profits notified at the beginning. And the total amount of financing available must be managed professionally so as not to become a problematic financing. At BMT Assyafi'iyah Berkah Nasional, this professionalism is realized in the form of a Financing Committee. This research is a field research which is qualitative descriptive. Data collection techniques using observation, interviews and documentation. The subjects in this study were the Business Director and Head of the Financing Division of KSPPS BMT Assyafi'iyah Berkah Nasional, while the object of this study was all activities related to the Financing Committee in the KSPPS BMT Assyafi'iyah Berkah Nasional. The results of the study explain that problematic financing at BMT Assyafi'iyah is caused by 3 factors, namely financing members, BMT internal factors, and external factors. Its function is to minimize problem financing by analyzing the feasibility of providing financing through the 5C principle approach which includes Character, Capacity, Capital, and Colleteral.